Oil-water separation ultrafiltration membrane as well as preparation method and application thereof

By introducing F127-COOH and PEI@CNT on the oil-water separation ultrafiltration membrane surface, integrating the coordinated anti-pollution mechanism of surface micro-nano structure and polymer-nanomaterial compatibility, the problem of flux reduction caused by oil droplet blocking membrane pores in the prior art is solved, and high throughput and excellent self-cleaning ability are achieved.

CN119607916AInactive Publication Date: 2025-03-14天津大学浙江研究院
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411948181.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

It is difficult to develop an oil-water separation ultrafiltration membrane with high throughput and excellent anti-pollution performance in the prior art, and oil droplets tend to clog the membrane pores and lead to a decrease in flux.

Method used

The hydrophilicity and roughness of the membrane are enhanced by introducing hydrophilic polymer F127-COOH and nanomaterial PEI@CNT on the membrane surface, integrating the coordinated anti-fouling mechanism of surface micro-nano structure and polymer-nanomaterial compatibility.

Benefits of technology

The high throughput and excellent self-cleaning capacity of the oil-water separation ultrafiltration membrane are achieved, with a flux of up to 571.52L/m2/h/bar, a total flux drop rate of 14.18%, and a flux recovery rate of nearly 100%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119607916A_ABST
    Figure CN119607916A_ABST
Patent Text Reader

Abstract

The invention provides an oil-water separation ultrafiltration membrane as well as a preparation method and application thereof. The invention relates to a preparation method of a water separation ultrafiltration membrane, which comprises the following steps: dissolving pluronic F127 and beta-carboxyethyl acrylate in deionized water under inert gas, adding an initiator, stirring, carrying out polymerization reaction at 60 DEG C for 6-12 hours, dialyzing to obtain a liquid product, and drying the liquid product to obtain F127-COOH copolymer powder; the preparation method comprises the following steps: dissolving a polyethyleneimine aqueous solution in deionized water, adding CNTs, and carrying out ultrasonic treatment and standing to obtain a PEI-coated CNT dispersion liquid; centrifuging the PEI (at) CNT dispersion liquid, and collecting supernate, so as to obtain a PEI (at) CNT nano material; adding polyvinylidene fluoride and an F127-COOH copolymer into an organic solvent to form a membrane casting solution, defoaming, and blade-coating the surface of a substrate with the membrane casting solution; and finally, immersing the substrate coated with the membrane casting solution in a coagulating bath added with the PEI-coated CNT nano material to form a membrane, and immersing the membrane in ultrapure water to obtain the oil-water separation ultrafiltration membrane. The oil-water separation ultrafiltration membrane provided by the invention realizes hydrophilicity and also has underwater super-oleophobicity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to the technical field of membrane preparation, and in particular to an oil-water separation ultrafiltration membrane and a preparation method and application thereof. Background Art

[0002] Oily wastewater has become a major problem in practical applications due to its wide range of sources and huge amount. Ultrafiltration membrane technology is widely regarded as a key method for oily wastewater treatment due to its simple operation and low energy consumption. However, during the separation process, oil droplets easily clog the membrane pores, resulting in a decrease in flux. Therefore, there is an urgent need to develop ultrafiltration membranes with high flux and excellent anti-fouling performance.

[0003] Membrane surface modification is the main strategy for designing anti-fouling membranes for oil-water separation, which is usually achieved by adjusting the chemical composition and micro-nanostructure of the membrane surface. Attempts have been made to introduce hydrophilic surfaces on originally hydrophobic membranes. Yang et al. formed a microstructured hydrogel layer by sequentially dip-coating polyethyleneimine and sodium alginate on the membrane surface, which made the membrane superhydrophilic. Hydrophilic polymers, characterized by their extensive hydrogen bond networks, exhibit excellent water binding and retention abilities, which help to form a strong hydration layer on the membrane surface. This hydration layer acts as a physical barrier to prevent the adhesion of oil stains, giving the membrane hydrophilicity and underwater superoleophobic properties. In addition, constructing micro-nanostructured surfaces by introducing nanomaterials is also considered as a way to enhance anti-fouling properties. Yang et al. achieved superhydrophilicity and underwater superoleophobicity by co-depositing carbon nanotubes (CNTs) modified with polydopamine and sodium polystyrene sulfonate on cotton fabric. This micro-nanostructure not only enhances the surface roughness of the membrane, but also increases the contact area between the membrane and water, thereby improving the permeation flux. At the same time, it promotes the formation of underwater Cassie state and achieves superoleophobic performance, with an underwater oil contact angle of more than 150°. Therefore, it can be expected that by optimizing the chemical composition and micro-nanostructure, the hydrophilicity and roughness of the membrane surface can be enhanced by using hydrophilic polymers and nanomaterials to modify the membrane surface. This in turn will significantly improve the membrane's ability to resist oil pollution.

[0004] In order to prepare hydrophilic and underwater superoleophobic membranes, various methods such as surface coating, grafting and in situ blending have been widely explored to introduce hydrophilic polymers and nanomaterials on the membrane surface for anti-fouling modification. However, the development of ultrafiltration membranes for oil-water separation that integrate the synergistic anti-fouling mechanism of surface micro-nanostructures and polymer-nanomaterial compatibility remains a major challenge. Summary of the invention

[0005] The present disclosure provides an oil-water separation ultrafiltration membrane and a preparation method and application thereof, so as to at least solve one of the technical problems existing in the prior art.

[0006] According to a first aspect of the present disclosure, a method for preparing a water separation ultrafiltration membrane is provided, the preparation method comprising:

[0007] F127-COOH copolymer preparation:

[0008] Under inert gas, Pluronic F127 and β-carboxyethyl acrylate were dissolved in deionized water, an initiator was added, the mixture was stirred, and a polymerization reaction was carried out at 60° C. for 6 to 12 hours, followed by dialysis to obtain a liquid product, and then the liquid product was dried to obtain a F127-COOH copolymer powder;

[0009] Preparation of PEI@CNT nanomaterials:

[0010] The polyethyleneimine aqueous solution is dissolved in deionized water, and after it is completely dissolved, CNTs are added, ultrasonicated, and allowed to stand to obtain a PEI@CNT dispersion; the PEI@CNT dispersion is then centrifuged and the supernatant is collected to obtain a PEI@CNT nanomaterial;

[0011] Membrane preparation:

[0012] The polyvinylidene fluoride and F127-COOH copolymer powders are added to an organic solvent, stirred until completely dissolved to form a casting liquid, degassed, and then the casting liquid is scraped on the surface of a substrate; finally, the substrate coated with the casting liquid is immersed in a coagulation bath added with PEI@CNT nanomaterials to form a film, and the membrane is immersed in ultrapure water for washing to obtain the oil-water separation ultrafiltration membrane.

[0013] In one embodiment, the initiator is Ce(NH 4 ) 2 (NO 3 ) 6 Dissolved in 1 mol L -1 HNO 3 The Ce(NH 4 ) 2 (NO 3 ) 6 With HNO 3 The molar volume ratio is 2mmol:20ml.

[0014] In one embodiment, the β-carboxyethyl acrylate, Pluronic F127 and Ce in the initiator 4+ The molar ratio is 60-70:0.5-2:2-10.

[0015] In one embodiment, in the preparation of the PEI@CNT nanomaterial, the mass volume ratio of the polyethyleneimine aqueous solution, deionized water and CNTs is 1200 mg:40 ml:20-50 mg.

[0016] In one embodiment, in the preparation of the membrane, the mass ratio of the polyvinylidene fluoride, F127-COOH copolymer powder, and the organic solvent is 1:0.8:8.2.

[0017] In one embodiment, during the film preparation, the concentration of the PEI@CNT nanomaterial in the coagulation bath is 0.5 to 6 mg.mL -1 .

[0018] In one embodiment, during the film preparation, the concentration of the PEI@CNT nanomaterial in the coagulation bath is 4 to 6 mg.mL -1 .

[0019] In one embodiment, in the film preparation, the organic solvent is a mixture of one or more of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0020] According to the second aspect of the present disclosure, the present invention further provides an oil-water separation ultrafiltration membrane, which is prepared by the preparation method in any one of the above-mentioned embodiments.

[0021] According to the third aspect of the present disclosure, the present invention also provides an application of an oil-water separation ultrafiltration membrane in oil-water separation.

[0022] Compared with the prior art, the advantages of the present application are: 1) The present application proposes a strategy for simultaneous modification of hydrophilicity and roughness, adding the synthesized F127-COOH and PEI@CNT to the casting solution and the coagulation bath respectively, integrating the synergistic anti-pollution mechanism of the surface micro-nano structure and the compatibility of polymer-nanomaterials to realize the preparation of anti-pollution membrane for oil-water separation.

[0023] 2) During the preparation of the ultrafiltration membrane of the present application, during the non-solvent induced phase separation (NIPS) process, F127-COOH can anchor PEI@CNT on the membrane surface through electrostatic interaction, and simultaneously enhance the hydrophilicity and roughness of the membrane, thereby achieving an enhanced anti-fouling performance mechanism.

[0024] 3) The oil-water separation ultrafiltration membrane of the present application has long-term structural stability and excellent self-cleaning ability.

[0025] 4) The oil-water separation ultrafiltration membrane flux of this application is as high as 571.52L / m 2 / h / bar. The total flux decline rate was 14.18%, and the flux recovery rate was close to 100%.

[0026] 5) The oil-water separation ultrafiltration membrane prepared by the method of the present application achieves hydrophilicity and has underwater superoleophobicity.

[0027] It should be understood that the content described in this section is not intended to identify the key or important features of the embodiments of the present disclosure, nor is it intended to limit the scope of the present disclosure. Other features of the present disclosure will become easily understood through the following description. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] The above and other objects, features and advantages of the exemplary embodiments of the present disclosure will become readily understood by reading the detailed description below with reference to the accompanying drawings. In the accompanying drawings, several embodiments of the present disclosure are shown in an exemplary and non-limiting manner, in which:

[0029] In the drawings, the same or corresponding reference numerals represent the same or corresponding parts.

[0030] Figure 1 A schematic diagram of preparing the oil-water separation ultrafiltration membrane disclosed in the present invention is shown;

[0031] Figure 2 The performance test results of the F127-COOH copolymer and PEI@CNT nanomaterial disclosed in the present invention are shown in FIG. Figure 2 a is the synthesis process of F127-COOH copolymer, Figure 2 b is the Fourier transform infrared spectrum of F127-COOH copolymer, Figure 2 c is the Fourier transform infrared spectra of carbon nanotubes CNTs, polyethyleneimine PEI and PEI@CNT nanomaterials. Figure 2 d is the transmission electron microscope image of PEI@CNT nanomaterials 1, Figure 2 e is a transmission electron microscope image of PEI@CNT nanomaterials 2);

[0032] Figure 3 The surface morphology and cross-sectional morphology of the ultrafiltration membrane prepared in each embodiment and comparative example of the present disclosure are shown ( Figure 3 a1- Figure 3 a4 is the surface morphology image of each ultrafiltration membrane, Figure 3 b1- Figure 3 b4 is a cross-sectional morphological image of each ultrafiltration membrane);

[0033] Figure 4 The pure water flux, flux recovery and total resistance change rate of the ultrafiltration membrane prepared in each embodiment and comparative example of the present disclosure are shown. Figure 4 a is the pure water flux diagram of each ultrafiltration membrane, Figure 4 b is the flux recovery rate FRR and total resistance change rate DR of each ultrafiltration membrane t picture, Figure 4 c is the flux recovery diagram of ultrafiltration membrane PEI@CNT-4 for three kinds of oil pollution. Figure 4d is the flux recovery rate FRR and total resistance change rate DRt of ultrafiltration membrane PEI@CNT-4 for three kinds of oil pollutants). DETAILED DESCRIPTION

[0034] In order to make the purpose, features, and advantages of the present disclosure more obvious and easy to understand, the technical solutions in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present disclosure.

[0035] In this application, inspired by electrostatically enhanced reaction surface segregation and functional modification of nanomaterials, a strategy for simultaneous modification of hydrophilicity and roughness is proposed for the preparation of ultrafiltration membranes for oil-water separation. The synthesized F127-COOH and PEI@CNT are added to the casting solution and the coagulation bath, respectively. During the non-solvent induced phase separation (NIPS) process, F127-COOH can anchor PEI@CNT on the membrane surface through electrostatic interactions, and simultaneously enhance the hydrophilicity and roughness of the membrane, thereby achieving an enhanced anti-fouling performance mechanism. The flux of the ultrafiltration membrane of this application is as high as 571.52L / m 2 / h / bar. The total flux decline rate is 14.18%, and the flux recovery rate is close to 100%. In addition, the ultrafiltration membrane of the present application also exhibits long-term structural stability and excellent self-cleaning ability.

[0036] Based on this, according to one embodiment of the present disclosure, the present invention provides a method for preparing an oil-water separation ultrafiltration membrane, comprising:

[0037] F127-COOH copolymer preparation:

[0038] Under inert gas, Pluronic F127 and β-carboxyethyl acrylate were dissolved in deionized water, and an initiator was added, and polymerization was carried out at 60° C. for 6 to 12 hours under stirring, and dialyzed to obtain a liquid product, and then the liquid product was dried to obtain F127-COOH copolymer powder;

[0039] Preparation of PEI@CNT nanomaterials:

[0040] The polyethyleneimine aqueous solution is dissolved in deionized water, and after it is completely dissolved, carbon nanotubes CNTs are added, ultrasonicated, and allowed to stand to obtain a PEI@CNT dispersion; the PEI@CNT dispersion is then centrifuged and the supernatant is collected to obtain a PEI@CNT nanomaterial;

[0041] Membrane preparation:

[0042] The polyvinylidene fluoride and F127-COOH copolymer powders are added to an organic solvent, stirred until completely dissolved to form a casting liquid, degassed, and then the casting liquid is scraped on the surface of a substrate; finally, the substrate coated with the casting liquid is immersed in a coagulation bath added with PEI@CNT nanomaterials to form a film, and the membrane is immersed in ultrapure water for washing to obtain the oil-water separation ultrafiltration membrane.

[0043] This application proposes a strategy for simultaneous modification of hydrophilicity and roughness, adding the synthesized F127-COOH and PEI@CNT to the casting solution and the coagulation bath respectively, integrating the synergistic anti-pollution mechanism of surface micro-nanostructure and polymer-nanomaterial compatibility to realize the preparation of anti-pollution membrane for oil-water separation.

[0044] In the non-solvent induced phase separation (NIPS) process, Pluronic F127 grafted with negatively charged carboxyl groups anchored the positively charged PEI@CNT on the membrane surface in situ through electrostatic interaction. The segregation enhancement caused by electrostatic interaction achieved the hydrophilicity and underwater superoleophobic modification of the hydrophobic PVDF membrane.

[0045] Wherein, in step 1), the initiator is Ce(NH 4 ) 2 (NO 3 ) 6 Dissolved in 1 mol L -1 HNO 3 The Ce(NH 4 ) 2 (NO 3 ) 6 With HNO 3 The molar volume ratio is 2mmol:20ml.

[0046] Preferably, β-carboxyethyl acrylate, Pluronic F127 and Ce in the initiator 4+ The molar ratio is 60-70:0.5-2:2-10. Exemplarily, 0.4 mmol of Pluronic F127 and 25.6 mmol of β-carboxyethyl acrylate are dissolved in 80 mL of deionized water (the molar ratio of β-carboxyethyl acrylate to F127 is 64:1); and 20 mL of initiator is added.

[0047] Among them, the synthetic reaction equation of F127-COOH is as follows Figure 2 As shown in a, β-carboxyethyl acrylate and Pluronic F127 were polymerized at 60°C for 8 hours under the catalysis of an initiator to obtain a F127-COOH copolymer.

[0048] Preferably, in the preparation of the F127-COOH copolymer, the stirring rate is 700 to 2000 rpm;

[0049] The dialysis was performed using a dialysis bag with a molecular weight of 14000Da for 7 days;

[0050] The liquid product is dried by sequentially using a rotary evaporator and a freeze dryer to dry the liquid product.

[0051] Preferably, in the preparation of PEI@CNT nanomaterials, the mass volume ratio of polyethyleneimine aqueous solution, deionized water and CNTs is 1200mg:40ml:20-50mg. More preferably, in the preparation of the PEI@CNT nanomaterials, the mass volume ratio of polyethyleneimine aqueous solution, deionized water and CNTs is 1200mg:40ml:40mg.

[0052] The ultrasonic treatment time is 30 min;

[0053] The centrifuging of the PEI@CNT dispersion is to centrifuge the PEI@CNT dispersion at a speed of 8000 rpm for 30 minutes.

[0054] Preferably, in the preparation of the membrane, the mass ratio of the polyvinylidene fluoride, F127-COOH copolymer powder and the organic solvent is 1:0.8:8.2.

[0055] During the film preparation, the stirring conditions were as follows: stirring temperature 80° C., stirring speed 700 rpm, and stirring time 8 h.

[0056] Preferably, in the preparation of the membrane, the degassing conditions are: placing the casting solution at 60° C. for 12 hours to remove bubbles; the coagulation bath temperature is 25° C. and the membrane forming time is 5 minutes.

[0057] Preferably, the concentration of PEI@CNT nanomaterials in the coagulation bath is 0.5 to 6 mg.mL -1 More preferably, in the membrane preparation, the concentration of the PEI@CNT nanomaterial in the coagulation bath is 4 to 6 mg.mL -1 .

[0058] Preferably, in the film preparation, the organic solvent includes but is not limited to: dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone.

[0059] In a second aspect, the embodiments of the present disclosure also provide an oil-water separation ultrafiltration membrane, which is prepared by the preparation method described above.

[0060] In a third aspect, the embodiments of the present disclosure also provide the application of the oil-water separation ultrafiltration membrane in oil-water separation.

[0061] The present application is further described in detail below with reference to specific embodiments:

[0062] Example 1

[0063] A method for preparing an oil-water separation ultrafiltration membrane comprises the following steps:

[0064] Step (1) Preparation of F127-COOH copolymer powder:

[0065] F127-COOH copolymer is synthesized by emulsion polymerization. Specifically including:

[0066] Under nitrogen protection, 0.4 mmol of Pluronic F127 and 25.6 mmol of β-carboxyethyl acrylate were dissolved in a three-necked flask filled with 80 mL of deionized water (the molar ratio of β-carboxyethyl acrylate to F127 was 64:1). Before the experiment, nitrogen was introduced for 60 minutes to remove oxygen. 20 mL of initiator (2.0 mmol of Ce(NH 4 ) 2 (NO 3 ) 6 Dissolve in 20 ml, 1 mol L -1 HNO 3 The polymerization reaction was carried out at 700 rpm and 60° C. for 8 hours. The unreacted components and oligomers were removed using a dialysis bag with a molecular weight of 14,000 Da for 7 days. The liquid product was then dried using a rotary evaporator and a freeze dryer. Finally, F127-COOH copolymer powder was obtained.

[0067] Step (2) Preparation of PEI@CNT nanomaterials:

[0068] Dissolve 1200 mg of polyethyleneimine (PEI) (50 wt% aqueous solution) in 40 mL of deionized water. After PEI is fully dissolved, add 40 mg of CNTs to the PEI-deionized water mixed solution. Then, use ultrasonic treatment for 30 minutes to promote the complete reaction of the amino groups in PEI with the carboxyl groups on the surface of CNTs. After standing for 12 hours, centrifuge the prepared PEI@CNT dispersion at 8000 rpm for 30 minutes. Collect the supernatant to obtain PEI@CNT nanomaterials for subsequent experiments. After calibration, the concentration of nanomaterials in the supernatant is 30 mg mL -1 .

[0069] Step (3) membrane preparation:

[0070] The membranes were prepared by non-solvent induced phase separation method (e.g. Figure 1 Specifically:

[0071] 1 g of polyvinylidene fluoride (PVDF) particles and 0.8 g of F127-COOH copolymer powder were dissolved in 8.2 g of dimethyl sulfoxide (DMSO) solution and stirred continuously at 80 °C and 700 rpm for 8 hours until they were completely dissolved to form a casting solution. Then, it was placed in an oven at 60 °C for 12 hours to remove bubbles. The casting solution was quickly poured on the top of the glass plate, and the solution was evenly scraped from top to bottom with a steel scraper to completely cover the glass plate. Finally, the glass plate was immersed in a coagulation bath at 25 °C for 5 minutes to form a film (the concentration of PEI@CNT nanomaterials in the coagulation bath was 0.5 mg mL -1 ), and then peel the membrane from the glass plate. The obtained membrane was immersed in ultrapure water for 24 hours, during which the water was changed three times to obtain an oil-water separation ultrafiltration membrane. The performance of the oil-water separation ultrafiltration membrane was then evaluated.

[0072] Example 2

[0073] The preparation of Example 2 is substantially the same as that of Example 1, except that in step 3), the concentration of PEI@CNT nanomaterial in the coagulation bath is 1 mg mL -1 .

[0074] Example 2 An oil-water separation ultrafiltration membrane was prepared.

[0075] Example 3

[0076] The preparation of Example 3 is substantially the same as that of Example 1, except that in step 3), the concentration of PEI@CNT nanomaterial in the coagulation bath is 2 mg mL -1 .

[0077] Example 3: An oil-water separation ultrafiltration membrane was prepared.

[0078] Example 4

[0079] The preparation of Example 4 is substantially the same as that of Example 1, except that in step 3), the concentration of PEI@CNT nanomaterial in the coagulation bath is 4 mg mL -1 .

[0080] Example 4: An oil-water separation ultrafiltration membrane was prepared.

[0081] Example 5

[0082] The preparation of Example 5 is substantially the same as that of Example 1, except that in step 3), the concentration of PEI@CNT nanomaterial in the coagulation bath is 6 mg mL -1 .

[0083] Example 5 An oil-water separation ultrafiltration membrane was prepared.

[0084] Comparative Example 1

[0085] The preparation of this comparative example 1 is substantially the same as that of Example 1, except that: in this comparative example 1, F127-COOH copolymer powder is not prepared; the F127-COOH powder in step 3) is replaced by F127; and the concentration of PEI@CNT nanomaterial in the coagulation bath is 0.

[0086] Comparative Example 1 prepared an ultrafiltration membrane.

[0087] Comparative Example 2

[0088] The preparation of this comparative example 2 is substantially the same as that of Example 1, except that: in this comparative example 2, F127-COOH copolymer powder is not prepared; the F127-COOH copolymer powder in step 3) is replaced by F127; and the concentration of PEI@CNT nanomaterial in the coagulation bath is 4 mg mL -1 .

[0089] Comparative Example 2 prepared an ultrafiltration membrane.

[0090] Comparative Example 3

[0091] The preparation of this comparative example 3 is substantially the same as that of example 1, except that in step 3), the concentration of the PEI@CNT nanomaterial in the coagulation bath is 0 mg mL -1 .

[0092] Comparative Example 3 prepared an oil-water separation ultrafiltration membrane.

[0093] In order to clearly distinguish the difference between this embodiment and the comparative example, the casting solution formula and coagulation bath required for the ultrafiltration membrane prepared in the above embodiment and the comparative example are listed in Table 1.

[0094] Table 1 Ultrafiltration membranes prepared in various embodiments and comparative examples and the required casting solution formula and coagulation bath composition

[0095]

[0096] Characterization and Testing:

[0097] 1) The F127-COOH copolymer powder prepared in Example 1 was subjected to infrared spectrum test. The results are as follows Figure 2 As shown in b.

[0098] Fourier transform infrared spectroscopy (FT-IR) was used to analyze the functional groups of F127-COOH. The FT-IR spectrum of the prepared F127-COOH copolymer is shown in Figure 2 b. The comparison results show that only F127-COOH has a peak at 1730 cm -1A peak is shown at , which corresponds to the stretching vibration of the ester group. The molar ratio of F127 to β-COOH (i.e., β-carboxyethyl acrylate) is calculated by 1 The calculated area ratio of the two copolymers was about 64:1, indicating that the F127-COOH copolymer was successfully synthesized.

[0099] II): The PEI@CNT nanomaterial prepared in step 2) of Example 1 was subjected to infrared spectrum test:

[0100] In step 2), after ultrasonic treatment, the amino groups of polyethyleneimine (PEI) and the carboxyl groups of carbon nanotubes (CNT) undergo a condensation reaction, thereby forming a covalent bond between them. The Fourier transform infrared spectra (FT-IR) of CNT, PEI and PEI@CNT are shown in FIG. Figure 2 As shown in c. Since CNT contains a large number of carboxyl groups, -1 There is an obvious -OH peak at 1380cm -1 There is a stretching vibration band of CO at 3000-3500cm -1 There is an obvious NH stretching vibration peak at 1633 cm. After modification, the CO stretching vibration band disappears, while the C=O and CN stretching vibrations are retained. In addition, due to the formation of amide bonds, the CNT at 1633 cm -1 The C=O bond stretching vibration peak in PEI@CNT shifts to 1659 cm -1 FT-IR successfully demonstrated the synthesis of PEI@CNT nanomaterials.

[0101] In addition, typical transmission electron microscopy (TEM) images of PEI@CNT nanomaterials are shown in Figure 2. Figure 2 d and Figure 2 The polyethyleneimine nanocoating is evenly present on the carbon nanotubes, and the high-resolution TEM image of a single carbon nanotube shows that the thickness of the nanocoating on the carbon nanotube is about 1.83 nm, which proves that PEI has successfully modified CNTs.

[0102] III): The surface morphology of the oil-water separation ultrafiltration membrane (hereinafter referred to as "membrane") prepared in the above examples and comparative examples was observed using a scanning electron microscope. Figure 3 shown.

[0103] Scanning electron microscopy (SEM) was used to observe the surface morphology of the membrane. Figure 3As shown in the figure, all membranes have a complete cortex. The surface morphology of the ultrafiltration membrane of comparative example 1, PVDF / F127, is relatively flat, with many regularly arranged small pores, and its cross-sectional morphology presents a typical finger-like pore structure. When -COOH is grafted onto F127, irregular pores appear on the membrane surface ( Figure 3 a1). PVDF and F127-COOH are both negatively charged, so they repel each other, resulting in uneven mixing. As the concentration of PEI@CNT increases, the uneven pores on the membrane surface gradually disappear, while some raised wrinkles gradually appear. Figure 3 As shown in a3, the characteristic nitrogen element of PEI@CNT is evenly distributed on the membrane surface. These results indicate that PEI@CNT has been successfully anchored on the membrane surface.

[0104] IV): The pure water flux results of the oil-water separation ultrafiltration membranes prepared in the above comparative examples and embodiments are as follows Figure 4 As shown in a.

[0105] The pure water flux of the ultrafiltration membrane of Comparative Example 1 (PVDF / F127) is about 775.42 L m -2 h -1 bar -1 This is because the addition of F127 accelerates the phase separation rate and forms uniform pores on the membrane surface. -1 When -2 h -1 bar -1 As the concentration increases, the water permeability gradually increases and eventually remains stable. Example 5 --- The water permeability of PEI@CNT-6 is 571.52 L m -2 h -1 bar -1 , which is the same as Example 4---PEI@CNT-4. This phenomenon can be explained by the coverage of PEI@CNT nanomaterials, which provides the membrane surface with a striped structure and hydrophilicity of the amino chain segments.

[0106] V): The flux recovery rate and total resistance change rate of the oil-water separation ultrafiltration membrane prepared in the above comparative examples and embodiments are as follows Figure 4 As shown in b.

[0107] The flux recovery rate (FRR) and total resistance change rate (DR) of the membrane t )like Figure 4 b. FRR and DR of ultrafiltration membrane of comparative example 1---PVDF / F127 tThe FRR of the membrane was gradually improved when PEI@CNT was introduced, and the DR t When the PEI@CNT concentration is 4 mg mL -1 and 6 mg mL -1 The antifouling performance of the membrane is the best when the FRR of PEI@CNT-4 and PEI@CNT-6 membranes are 99.62% and 99.4%, respectively. t The percentages of NH4+ and NH4+ are 14.18% and 14.7%, respectively, which are basically the same. This is attributed to the enhanced antifouling mechanism. Since the amino-modified carbon nanotubes have the highest coverage of the membrane surface, the roughness and hydrophilicity of the membrane are greatly improved, which limits the adhesion of pollutants on the membrane surface and releases the pollutants with a simple water rinse.

[0108] In addition, if Figure 4 c and Figure 4 As shown in Figure d, vacuum pump oil, hexadecane oil and silicone oil were used to demonstrate the versatility of Example 4---PEI@CNT-4. The membrane showed excellent interception and antifouling properties for all three pollutants, demonstrating the versatility of the membrane. As for the separation mechanism, on the one hand, the rough surface helps the membrane to construct a Cassie-Baxter state underwater, thereby limiting the interaction between oil droplets and the surface. On the other hand, the large number of amino groups on the membrane surface make the membrane highly hydrophilic, enhance the interaction between water molecules and the surface, and form a dense and stable hydration layer.

[0109] It should be understood that the various forms of processes shown above can be used to reorder, add or delete steps. For example, the steps recorded in this disclosure can be executed in parallel, sequentially or in different orders, as long as the desired results of the technical solutions disclosed in this disclosure can be achieved, and this document does not limit this.

[0110] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of the features. In the description of the present disclosure, the meaning of "plurality" is two or more, unless otherwise clearly and specifically defined.

[0111] The above is only a specific embodiment of the present disclosure, but the protection scope of the present disclosure is not limited thereto. Any person skilled in the art who is familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present disclosure, which should be included in the protection scope of the present disclosure. Therefore, the protection scope of the present disclosure should be based on the protection scope of the claims.

Claims

1. A method for preparing an oil-water separation ultrafiltration membrane, characterized in that: The preparation method comprises: F127-COOH copolymer preparation: Under inert gas, Pluronic F127 and β-carboxyethyl acrylate were dissolved in deionized water, an initiator was added, the mixture was stirred, a polymerization reaction was carried out at 60° C. for 6 to 12 hours, the mixture was dialyzed, a liquid product was obtained, and the mixture was dried to obtain a F127-COOH copolymer powder; Preparation of PEI@CNT nanomaterials: The polyethyleneimine aqueous solution is dissolved in deionized water, and after it is completely dissolved, CNTs are added, ultrasonicated, and allowed to stand to obtain a PEI@CNT dispersion; the PEI@CNT dispersion is then centrifuged and the supernatant is collected to obtain a PEI@CNT nanomaterial; Membrane preparation: The polyvinylidene fluoride and F127-COOH copolymer powders are added to an organic solvent, stirred until completely dissolved to form a casting liquid, degassed, and then the casting liquid is scraped on the surface of a substrate; finally, the substrate coated with the casting liquid is immersed in a coagulation bath added with PEI@CNT nanomaterials to form a film, and the membrane is immersed in ultrapure water for washing to obtain the oil-water separation ultrafiltration membrane.

2. The preparation method according to claim 1, characterized in that: The initiator is Ce(NH4)2(NO3)6 dissolved in 1 mol L -1 It is obtained from HNO3, and the molar volume ratio of Ce(NH4)2(NO3)6 to HNO3 is 2mmol:20ml.

3. The preparation method according to claim 2, characterized in that: The β-carboxyethyl acrylate, Pluronic F127 and Ce in the initiator 4+ The molar ratio is 60-70:0.5-2:2-10.

4. The preparation method according to claim 1, characterized in that: In the preparation of the PEI@CNT nanomaterial, the mass volume ratio of the polyethyleneimine aqueous solution, deionized water and CNTs is 1200 mg:40 ml:20-50 mg.

5. The preparation method according to claim 1, characterized in that: In the film preparation, the mass ratio of the polyvinylidene fluoride, F127-COOH copolymer powder and the organic solvent is 1:0.8:8.

2.

6. The preparation method according to claim 1, characterized in that: In the film preparation, the concentration of PEI@CNT nanomaterial in the coagulation bath is 0.5-6 mg.mL -1 .

7. The preparation method according to claim 6, characterized in that: In the film preparation, the concentration of PEI@CNT nanomaterial in the coagulation bath is 4-6 mg.mL -1 .

8. The preparation method according to claim 1, characterized in that: In the film preparation, the organic solvent is a mixture of one or more of dimethyl sulfoxide, N,N-dimethylformamide, and N-methylpyrrolidone.

9. An ultrafiltration membrane for oil-water separation, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 8.

10. Use of the oil-water separation ultrafiltration membrane according to claim 9 in oil-water separation.